1997
DOI: 10.1016/s0969-2126(97)00186-x
|View full text |Cite
|
Sign up to set email alerts
|

Barley lipid-transfer protein complexed with palmitoyl CoA: the structure reveals a hydrophobic binding site that can expand to fit both large and small lipid-like ligands

Abstract: . A comparison of the structures of bLTP in the free and bound forms suggests that bLTP can accommodate long olefinic ligands by expansion of the hydrophobic binding site. This expansion is achieved by a bend of one helix, HA, and by conformational changes in both the C terminus and helix HC. This mode of binding is different from that seen in the structure of maize nsLTP in complex with palmitic acid, where binding of the ligand is not associated with structural changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 50 publications
3
98
1
Order By: Relevance
“…2) returned a dissociation constant, K d , of 2^0.3 mm and number of sites, n, of 1.7^0.1. The affinity value (K d ) is in disagreement with the results from Lersche et al [7] who reported a K d higher than 10 22 m for various lysophosphatidylcholines. However, our result is analogous with the dissociation constant reported in the case of wheat LTP1 [10].…”
Section: Binding Of Myrgro-pcho By Native Barley Ltp1contrasting
confidence: 89%
See 1 more Smart Citation
“…2) returned a dissociation constant, K d , of 2^0.3 mm and number of sites, n, of 1.7^0.1. The affinity value (K d ) is in disagreement with the results from Lersche et al [7] who reported a K d higher than 10 22 m for various lysophosphatidylcholines. However, our result is analogous with the dissociation constant reported in the case of wheat LTP1 [10].…”
Section: Binding Of Myrgro-pcho By Native Barley Ltp1contrasting
confidence: 89%
“…The threedimensional structure of ns-LTP1 has been determined by 1H-NMR and crystallography and reveals a hydrophobic cavity within the protein [4±9]. Lersche et al [7] were the first to report a binding constant, K d , in the case of barley LTP1 with fatty acids, lysophosphatidylcholine and acylCoA. In contrast with wheat LTP1 [10], the affinity was very low with binding constants in the range 10 22 to 10 24 m, except for acyl-CoA where K d 10 26 m. In that study, the intrinsic tyrosine fluorescence was used to probe the binding of lipids.…”
mentioning
confidence: 99%
“…[4,[9][10][11][12][13][14][15][16][17][18] Crystal structures of maize nsLTP complexed with palmitate [10] and with an array of fatty acids ranging from C10 to C18, [11] wheat nsLTP in complex with lyso-myristoyl-phosphatidyl-choline (LMPC), [12] rice nsLTP complexed with stearate, [13] and peach nsLTP with bound laurate [14] have been determined by X-ray crystallography. Solution NMR structures of wheat nsLTP complexed with 1,2-dimyristoyl-phosphatidyl-glycerol [15] and with prostaglandin B 2 , [16] and barley nsLTP in complex with palmitoyl coenzyme A [17] and palmitate [18] have also been reported. In all these complexes, the hydrocarbon tail of the bound lipids is inserted into the hydrophobic cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, while the space groups of nsLTP-ligand crystal complexes available are different (P2 1 2 1 2 1 for maize and wheat complexes, P6 5 22 for the peach complex and C 2 for the rice complex), all of them agree in displaying the same orientation for the bound lipid. However, it is noted that the two NMR solution structures available for a same nsLTP (barley) complexed with either palmitoyl CoA [17] or palmitate [18] happen to show opposite orientations. This observation, which has been until now mostly ignored, is the major issue addressed in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Solution structures obtained by NMR spectroscopy have been reported for maize (Petit et al 1994;Gomar et al 1996;Lerche & Poulsen 1998), wheat (Simorre et al 1991;Gincel et al 1994;Sodano et al 1997;Tassin-Moindrot et al 2000), barley (Heinemann et al 1996;Lerche et al 1997;Lerche & Poulsen 1998), rice (Poznanski et al 1999) and onion (Tassin et al 1998). In addition, molecular modelling has been used to infer the lipid-binding properties of a cold-induced leaf LTP (Keresztessy & Hughes 1998) and a seed LTP from barley (Douliez et al 2001).…”
Section: Wax9 a Altcgtvnsnvapcigyitqggt-lpgacctgvsklnsmarttpdrqqacrclmentioning
confidence: 99%